Identification of microRNAs regulated by isothiocyanates and association of polymorphisms inside their target sites with risk of sporadic colorectal cancer - Slaby, Ondrej; Sachlova, Milana; Brezkova, Veronika; Hezova, Renata; Kovarikova, Alena; Bischofová, Svatava; Sevcikova, Sabina; Bienertova-Vasku, Julie; Vasku, Anna; Svoboda, Marek; Vyzula, Rostislav (Nutrition and cancer, 2013)
Sporadic colorectal cancer (CRC) is a typical multifactorial disease. Isothiocyanates (ITC) have been recently shown to inhibit development of CRC in many experimental models. MicroRNAs (miRNAs) are short noncoding RNAs that posttranscriptionally regulate gene expression through binding to 3' untranslated regions (3'UTR) of target mRNAs. MiRNAs are regulated by natural agents, ITCs included. In our study, using global expression profiling based on TaqMan Low-Density Arrays, we identified 3 common miRNAs (miR-155, miR-23b, miR-27b) regulated by ITCs (sulforaphane, iberin) in colonic epithelial cell lines NCM460 and NCM356. In silico predictions allowed us to find 9 relevant single nucleotide polymorphisms (SNPs) localized within the 3'UTRs of genes (AGTR1, TNFAIP2, PRKCB, HSPA9, RABGAP1, DICER1, ADAM19, VWA5A, and SIRT5) targeted by these ITC-related miRNAs. Finally, we observed that homozygous CC genotype of DICER1, rs1057035, was significantly associated with decreased risk of CRC (odds ratio = 0.49; 95% confidence interval: 0.25-0.95, P = 0.036) when compared to TT homozygote genotype; also, the C allele tended to have a protective effect (P = 0.072). This study showed that miRNAs could be involved in chemoprotective effects of natural agents; their function alteration through SNPs in their binding sites and flanking regions presents a new class of CRC risk factors.
Keywords: Computer Simulation; senioři; počítačová simulace; Polymorphism, Single Nucleotide; isothiokyanatany; Isothiocyanates; ochranné látky; Female; Male; Colorectal Neoplasms; Aged; Middle Aged; DEAD-box RNA Helicases; homozygot; regulace genové exprese; buněčné linie; Gene Expression Profiling; Homozygote; Gene Expression Regulation; 3' nepřekládaná oblast; Sulfoxides; DEAD-box RNA-helikasy; mikro RNA; sulfoxidy; mužské pohlaví; ženské pohlaví; kolorektální nádory; vazebná místa; Epithelial Cells; Protective Agents; Ribonuclease III; Binding Sites; epitelové buňky; ribonukleasa III; Cell Line; lidé středního věku; MicroRNAs; studie případů a kontrol; 3' Untranslated Regions; stanovení celkové genové exprese; lidé; Humans; jednonukleotidový polymorfismus; genetická predispozice k nemoci; Case-Control Studies; Genetic Predisposition to Disease